CHILDFREE: AN INDONESIAN RELIGIOUS AND CULTURAL PERSPECTIVE - Fathimah Pertiwi; Michael Sylvester Mitchel Vinco (BUANA GENDER : Jurnal Studi Gender dan Anak, 2023)
As a modern culture characterized by Western Culture, Childfree is a decision taken based on free agreement between husband and wife. However, there are still many who think that the Childfree decision is the result of problems experienced by the woman. This paper will discuss the phenomenon of childfree in Indonesia based on the views of Islam and Catholicism as the majority religions that influence the thoughts and perspectives of Indonesian society regarding childfree. This research method uses a literature study by using references from various open sources and scientific articles. Indonesia, which has an Eastern culture, generally rejects Childfree. A more collective Eastern view makes the relationship between husband, wife and child inseparable. Islam and Catholicism also reject Childfree. Islam, referring to the Qur'an, views that marriage is to continue good offspring so that one day they can become leaders of their group. Catholic Christianity based on the Holy Scriptures (Bible / Bible) states that the existence of children through intercourse is God's very good will as a form of love. In the official interpretation of the Catechism of the Catholic Church, the purpose of marriage is the welfare of husband and wife, the birth of children, and the education of children.